20th AIAA International Space Planes and Hypersonic Systems and Technologies Conference 2015
DOI: 10.2514/6.2015-3587
|View full text |Cite
|
Sign up to set email alerts
|

Experimental study of combustion oscillations in a dual-mode scramjet

Abstract: Characteristics of combustion oscillations were studied experimentally in a direct-connected supersonic combustion test facility with a cavity flameholder and transverse fuel injection from the wall.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2
2

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 8 publications
(8 reference statements)
1
2
0
Order By: Relevance
“…The intense oscillation displayed distinct peaks, occurring at a frequency of approximately 300 Hz. This frequency is relatively close to the reports of Allison [18], Tian [19], and Zhong et al [20]. Moreover, the pressure curve within a timeframe of 0.012 s was selected and aligned with the starting point in time, as depicted in Figure 8c.…”
Section: Concomitance Between Pressure Oscillation and Flame Surface ...supporting
confidence: 61%
See 1 more Smart Citation
“…The intense oscillation displayed distinct peaks, occurring at a frequency of approximately 300 Hz. This frequency is relatively close to the reports of Allison [18], Tian [19], and Zhong et al [20]. Moreover, the pressure curve within a timeframe of 0.012 s was selected and aligned with the starting point in time, as depicted in Figure 8c.…”
Section: Concomitance Between Pressure Oscillation and Flame Surface ...supporting
confidence: 61%
“…Allison et al [18] conducted experiments at the University of Virginia to investigate flame motion and stability in a cavity flame-stabilizer combustion chamber fueled by ethylene, finding periodic oscillations at 340 Hz. Tian et al [19] studied combustion oscillations in a similar combustion chamber using a direct-connected supersonic combustion facility and compared the results of wall static pressure FFT analysis at different conditions. Zhong et al [20] investigated dominant frequencies related to flame oscillations in a combustion chamber using a direct supersonic combustion facility, and established the characteristic frequency range of ethylene and mixed fuels as 49-317 Hz.…”
Section: Introductionmentioning
confidence: 99%
“…They found that the coupling between flow oscillations and unsteady heat release in the reaction zone leads to combustion instabilities. Using ethylene as fuel, Tian et al [29] investigated the effect of inlet Mach number and transverse injection on combustion instability and found the presence of a high frequency oscillation peak frequency of about 4 kHz at the trailing edge of the cavity. Similarly, Gao et al [30] investigated the effect on combustion instability when the equivalent ratio was in the range of 0.2 to 0.63.…”
Section: Introductionmentioning
confidence: 99%